High‐Pressure High‐Temperature Synthesis of Mixed Nitridosilicatephosphates and Luminescence of AESiP(3)N(7):Eu(2+) (AE=Sr, Ba) - Eisenburger, Lucien (Chemistry, 2021)
Tetrahedra‐based nitrides with network structures have emerged as versatile materials with a broad spectrum of properties and applications. Both nitridosilicates and nitridophosphates are well‐known examples of such nitrides that upon doping with Eu(2+) exhibit intriguing luminescence properties, which makes them attractive for applications. Nitridosilicates and nitridophosphates show manifold structural variability; however, no mixed nitridosilicatephosphates except SiPN(3) and SiP2N4NH have been described so far. The compounds AESiP(3)N(7) (AE=Sr, Ba) were synthesized by a high‐pressure high‐temperature approach using the multianvil technique (8 GPa, 1400–1700 °C) starting from the respective alkaline earth azides and the binary nitrides P(3)N(5) and Si(3)N(4). The latter were activated by NH(4)F, probably acting as a mineralizing agent. SrSiP(3)N(7) and BaSiP(3)N(7) were obtained as single crystals. They crystallized in the barylite‐1O (M=Sr) and barylite‐2O structure types (M=Ba), respectively, with P and Si being occupationally disordered. Cation disorder was further supported by solid‐state NMR spectroscopy and energy‐dispersive X‐ray spectroscopy (EDX) mapping of BaSiP(3)N(7) with atomic resolution. Upon doping with Eu(2+), both compounds showed blue emission under UV excitation.